Case Report: CNNM2 Mutations Cause Damaged Brain Development and Intractable Epilepsy in a Patient Without Hypomagnesemia - Li, Xiucui; Bao, Shijia; Wang, Wei; Shi, Xulai; Hu, Ying; Li, Feng; Zhao, Qianlei; Zheng, Feixia; Lin, Zhongdong (Frontiers in Genetics, 2021)
A series of neurological manifestations such as intellectual disability and epilepsy are closely related to hypomagnesemia. Cyclin M2 (CNNM2) proteins, as a member of magnesium (Mg2+) transporters, were found along the basolateral membrane of distal renal tubules and involved in the reabsorption of Mg2+. Homozygous and heterozygous mutations in CNNM2 reported so far were responsible for a variable degree of hypomagnesemia, several of which also showed varying degrees of neurological phenotypes such as intellectual disability and epilepsy. Here, we report a de novo heterozygous CNNM2 mutation (c.2228C>T, p.Ser743Phe) in a Chinese patient, which is the only mutation located in the cyclic nucleotide monophosphate-binding homology (CNBH) domain of CNNM2 proteins reported so far. The patient presented with mild intellectual disability and refractory epilepsy but without hypomagnesemia. Thus, we reviewed the literature and analyzed the phenotypes related to CNNM2 mutations, and then concluded that the number of mutational alleles and the changed protein domains correlates with the severity of the disease, and speculated that the CNBH domain of CNNM2 possibly plays a limited role in Mg2+ transport but a significant role in brain development. Furthermore, it can be speculated that neurological phenotypes such as intellectual disability and seizures can be purely caused by CNNM2 mutations.